Strategi Promosi Untuk Keberlangsungan Usaha Dari Penciptaan Kreasi Barang Bekas di Kelurahan Kembangan Selatan Jakarta Barat - Andriansyah Bachtillah; Supriyatno Supriyatno; Dewi Murtiningsih (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Waste management is one of the main challenges in achieving environmental sustainability. This community service program aims to develop a used goods creation business based on business and environmental sustainability in Kembangan Selatan Subdistrict. The methods used include outreach, training and assistance to local communities in processing used goods into products of economic value. Through this program, it is hoped that the community can improve their skills in processing waste, create new business opportunities, and reduce the amount of waste that pollutes the environment. The results of this activity show an increase in public awareness and participation in protecting the environment, as well as the formation of several new business groups engaged in recycling. Business sustainability is measured through indicators of increasing income and quality of life for the community. Thus, it is hoped that this program can become a business development model that is not only economically profitable, but also contributes positively to environmental sustainability